Informe de artillería y municiones en San Juan - Todd, Roberto H.; Rockwell, James Jr. (My University, 1898)
Informe de Artillería y municiones en San Juan. Copy of report on sea coast and siege artillery and ammunition transferred by spanish authorities in San Juan.
Keywords: Headquarters--United States--Troops in Puerto Rico.; Ammunition--Storage.; Municiones--Almacenamiento.